Sustainability and social marketing issues in Asia - Quoquab, Farzana, 1978-; Mohammad, Jihad, 1970- (Emerald Publishing Limited, 2023)
The complex issues of sustainability and social marketing are gaining increasing global attention. This increased concern for environmental welfare has started to affect the way marketers, managers and policy makers think and organize their businesses. In Western culture, there has been widespread discussion on green related issues; however, different cultures are at different stages in embracing this global change, and local conditions can greatly affect how strategies are enacted. Sustainability and Social Marketing Issues in Asia applies this discussion to Asian culture, using case studies that reflect the problems and success of nine countries - Malaysia, Brunei, the Philippines, Indonesia, Iran, Syria, Sri Lanka, India, and Pakistan - in adopting green and social marketing concepts. These concepts include: triple bottom line; social entrepreneurialism; sustainability marketing; green marketing; sustainable energy, sustainable agriculture, sustainable ecosystems, social development, waste management problem, refugee crisis, care for animals and corporate social responsibility. The cases outlined in this book illustrate how companies and organizations operating in Asian countries incorporate sustainability and environmental concepts into their social marketing strategy. It will appeal to researchers and practitioners, working in the fields of social marketing, consumer behavior, corporate social responsibility, organizational behavior and sustainability.